Analysis of Factors Related to the Use of Iud Contraceptives in the Working Area - Ikke Kristiya; Siti Nurhajjah; Hudila Rifa Karmia (Newinera Publisher, 2025)
The growth of the world's population is increasing day by day, the increase in the number of people also has an impact on the maternal mortality rate (AKI), The factor that causes the increase in population is the lack of people in the use of contraception, especially in the use of long-term contraception, one of which is IUD. The purpose of this study is to find out